2003
DOI: 10.1088/0022-3727/36/20/l02
|View full text |Cite
|
Sign up to set email alerts
|

Spin-coated zinc oxide transparent transistors

Abstract: A ZnO transparent thin-film transistor (TTFT) with a channel layer formed via spin-coating deposition is demonstrated. The TTFT is highly transparent and exhibits n-channel, enhancement-mode behaviour with a channel mobility as large as 0.20 cm2 V−1 s−1 and a drain current on-to-off ratio of nearly 107.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(182 citation statements)
references
References 17 publications
4
177
0
1
Order By: Relevance
“…It has been demonstrated that the electrical characteristics of ZnO films can be controlled by doping with ternary elements 6,7) or by heat treatment processes. 8,9) ZnO-based thin films have been prepared by various thin film deposition techniques, such as RF/DC magnetic sputtering deposition, pulsed laser deposition, chemical vapor deposition, chemical bath deposition, spray pyrolysis, sol-gel methods, etc. Use of solution-based processes to form oxide semiconductors may improve the manufacturing throughput of microelectrical devices by enabling maskless processes, including inkjet printing, 10) selective electroless plating, 11) etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the electrical characteristics of ZnO films can be controlled by doping with ternary elements 6,7) or by heat treatment processes. 8,9) ZnO-based thin films have been prepared by various thin film deposition techniques, such as RF/DC magnetic sputtering deposition, pulsed laser deposition, chemical vapor deposition, chemical bath deposition, spray pyrolysis, sol-gel methods, etc. Use of solution-based processes to form oxide semiconductors may improve the manufacturing throughput of microelectrical devices by enabling maskless processes, including inkjet printing, 10) selective electroless plating, 11) etc.…”
Section: Introductionmentioning
confidence: 99%
“…10,11) ZnO-based semiconductor films have been shown to be suitable for service as TFT active channel layers. [12][13][14][15] Kwon et al 16) indicated that to control the carrier density of the active layer in a ZnO-based TFT is a challenge, because the active layer supplies high carrier density that will be conducting when an applied gate voltage is absent. The ionic radius of Mg 2þ (0.065 nm) is smaller than Zn 2þ (0.074 nm), and thus the solid solubility limit of MgO in ZnO can approach 40 at%.…”
Section: Introductionmentioning
confidence: 99%
“…최근 열전소재로 반도체 나노물질 이 주목받고 있으며, 특히 나노입자 박막은 열전도도와 전기전도 도의 독립적인 조절로 고효율 열전발전의 가능성을 보여주고 있 다 [7,8]. 일반적으로 반도체 나노입자 박막은 유기용매에서 합성 되어진 나노입자 용액을 이용하여 제작할 수 있지만, 유기용매에 서 합성된 나노입자를 이용하여서는 유기용매에 취약한 플라스틱 소재위에 그 나노입자 박막을 형성시키기가 어렵다 [9,10] …”
Section: 서 론 최근 다기능 웨어러블 전자소자가 미래 성장산업의 한 분야로unclassified